Stenosis of the celiac trunk is associated with anastomotic leak after Ivor–Lewis esophagectomy. Issue 7 (1st March 2019) - Brinkmann, S; Chang, D H; Kuhr, K; Hoelscher, A H; Spiro, J; Bruns, C J; Schroeder, W
SUMMARY: Transthoracic esophagectomy with gastric tube formation is the surgical treatment of choice for esophageal cancer. The surgical reconstruction induces changes of gastric microcirculation, which are recognized as potential risk factors of anastomotic leak. This prospective observational study investigates the association of celiac trunk (TC) stenosis with postoperative anastomotic leak. One hundred fifty-four consecutive patients with esophageal cancer scheduled for Ivor–Lewis esophagectomy were included. Preoperative staging computed tomography (CT) was used to identify TC stenosis. Any narrowing of the lumen due to atherosclerotic changes was classified as stenosis. Percentage of stenotic changes was calculated using the North American Symptomatic Carotid Endarterectomy Trial formula. Multivariable analysis was used to identify possible risk factors for leak. The overall incidence of TC stenosis was 40.9%. Anastomotic leak was identified in 15 patients (9.7%). Incidence of anastomotic leak in patients with stenosis was 19.4% compared to 2.3% in patients without stenosis. Incidence of stenosis in patients with leak was 86.7% (13 of 15 patients) and significantly higher than 38.8% (54 of 139 patients) in patients without leak ( P < 0.001). There was a significant difference in median degree of TC stenosis (50.0% vs 39.4%; P = 0.032) in patients with and without leak. In the multivariable model, TC stenosis was an independent risk factor for anastomotic leak (odds ratio: 5.98, 95% CI: 1.58–22.61). TC stenosis is associated with postoperative anastomotic leak after Ivor–Lewis esophagectomy. Routine assessment of TC for possible stenosis is recommended to identify patients at risk.